Patellar height measurement in Indonesian normal adult population. (October 2022) - Mustamsir, Edi; Isnansyah, Yun; Phatama, Krisna Yuarno
Abstract: Background: Patellar height is the distance formed by the patella and the length of the patellar tendon. Patellar height measurement can predispose to various abnormalities in the knee joint. Patellar height can be measured using several sizes, such as the Insall-Salvati ratio (IS), Modified Insall-Salvati ratio (MIS), Caton-Deschamps index (CD), and the Blackburne-Peel (BP) index. In Indonesia, no data on the value of patellar height is available. This study aims to determine the patellar height value in Indonesians and compare if there are differences with the standard values commonly used by other countries. Matherials and methods: This study is descriptive with 136 research subjects aged 20–40. Data were taken from December 2021 to February 2022. The results of patellar X-ray were measured using the Insall-Salvati, Modified Insall-Salvati, Caton-Deschamps, and Blackburne-Peel methods. Results: In the measurement of patellar height, the longest measurement was found in the MIS measurement, while the shortest patellar height was measured using the BP method. The normal value of the IS method is 0.78–1.26, the MIS method is > 1.98, the CD method is 0.79–1.23, and the BP method is 0.70–1.10 for patellar height in Indonesia. This study also shows no significant difference in the value of patellar height between male and female sex using the IS measurement method. Conclusion: There is a difference in the standard value of patellar height, which is commonly used by other countries with the standard value of patellar height in Indonesia, but it is not significant. Highlights: Each country has different standard value of the patella height. Patellar height can be measured using several methods. Indonesian patellar height standard value different with other countries.